2019
DOI: 10.1186/s12933-019-0877-2
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin for Japanese patients with chronic heart failure and type II diabetes

Abstract: Background Reports that sodium glucose cotransporter 2 inhibitors decrease cardiovascular death and events in patients with diabetes have attracted attention in the cardiology field. We conducted a study of canagliflozin in patients with chronic heart failure and type II diabetes. Methods Thirty-five Japanese patients with chronic heart failure and type II diabetes were treated with canagliflozin for 12 months. The primary endpoints were the changes of subcutaneous, vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 28 publications
1
46
0
1
Order By: Relevance
“…Thus, instead of biopsy, it would be feasible to use VAT SUVmax as a surrogate marker of VAT inflammation in clinical practice. Recently, several randomized clinical trials have demonstrated that both novel drugs glucagon-like-peptide-1 (GLP-1) receptor agonist and sodium glucose cotransporter 2 inhibitors (SGLT2i) can reduce visceral adiposity thereby attenuating CVD risks [33][34][35]. Considering that the inflamed VAT is a causal mechanism which contributes to the development of CVD, it is conceivable that VAT SUVmax could be employed as a potential surrogate marker of VAT inflammation, thereby evaluating therapeutic effect of both GLP-1 receptor agonist and SGLT2i targeting inflamed VAT and its related CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, instead of biopsy, it would be feasible to use VAT SUVmax as a surrogate marker of VAT inflammation in clinical practice. Recently, several randomized clinical trials have demonstrated that both novel drugs glucagon-like-peptide-1 (GLP-1) receptor agonist and sodium glucose cotransporter 2 inhibitors (SGLT2i) can reduce visceral adiposity thereby attenuating CVD risks [33][34][35]. Considering that the inflamed VAT is a causal mechanism which contributes to the development of CVD, it is conceivable that VAT SUVmax could be employed as a potential surrogate marker of VAT inflammation, thereby evaluating therapeutic effect of both GLP-1 receptor agonist and SGLT2i targeting inflamed VAT and its related CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention for these risk factors and optimal glycemic control are the critical component of diabetes management. A recent study demonstrated that the use of sodium glucose cotransporter 2 inhibitors (SGLT2-is) reduces the risk of major cardiovascular events [51, 52]. In addition, the abnormal platelet activation observed in patients with DM is conducive to the formation of pathological thrombosis and the progression of cardiovascular diseases [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, beneficial effect of SGLT2i has also been suggested in patients with HFpEF: in an echocardiographic study by Soga et al the mitral E/e' ratio, LV-MI, and LAVI were decreased with dapagliflozin treatment among diabetic patients with high prevalence of HFpEF (69%) and HFmrEF (17%), whereas the improvement in LV systolic function and the reduction in BNP levels were minimal [31]. A recent prospective study of diabetic patients with HFpEF demonstrated reductions in E/e' ratio and BNP level, along with improved renal function, decreased fat volumes and reduced oxidative stress [32].…”
Section: Differences In Sglt2i Effects Between Hfref Vs Hfpefmentioning
confidence: 97%